Determinants of Foreign Direct Investment in Sri Lanka - Sooriyakumar, K.; Perera, S.P.M.P.; Sarujan, S. (University of Colombo Institute for Agro-Technology and Rural Sciences – Sri Lanka, 2025)
This study examines the macroeconomic determinants of Foreign Direct Investment (FDI) inflows in Sri Lanka over the period from 1970 to 2022. Key variables analyzed include FDI net inflows (as a percentage of GDP), exchange rates, GDP growth, inflation and trade openness. Using Autoregressive Distributed Lag (ARDL) model, the research captures both short-run and long-run relationships between these variables and FDI behavior. The results reveal that both GDP growth and trade openness are significant drivers of FDI, exerting positive effects in both the immediate and long-term contexts. Stronger economic expansion and liberalized trade environments are shown to enhance Sri Lanka’s investment appeal. Notably, while currency depreciation initially deters FDI, it exerts a positive influence over time, underscoring the complex role of exchange rate dynamics in investment decisions. Additionally lagged GDP- particularly with a two-period lag- proves influential, highlighting the importance of sustained economic performance in shaping investor confidence. In contrast, inflation and FDI in US dollar terms were found to have no significant impact on FDI inflows, suggesting that foreign investors weigh broader macroeconomic stability over inflationary pressures. The study concludes that policies fostering economic growth, ensuring exchange rate stability, and enhancing trade openness are crucial for attracting sustained foreign investment and driving long-term development in Sri Lanka.
Keywords: Auto regressive distributed lag model; Economic growth; Foreign direct investment; Macroeconomic determinants